PENGARUH TINGKAT PROTEIN RANSUM TERHADAP AMEn (APPARENT METABOLIZABLE ENERGY N CORRECTION) PADA ITIK MOJOSARI JANTAN DAN BETINA - Widodo, Ricky Maula; Fitasari, Eka; Supartini, Nonok (Fakultas Pertanian, 2017)
This study aims to determine the percentage of use of the best protein level in feed ration against AME and N correction on mojosari duck male and female grower phase due to the use of feed formulation with 3 different Protein content. Ducks used were male mojosari ducks and females grower phase (age ?4 weeks) with an average body weight of 1485 g ± 41.55. Field research using Completely Randomized Design of Native Patterns. The Factor 1: Sex (male and female) Factor 2: The protein level of each unit consists of 1 duck so that the total duck needed is 24 tail consisting of 12 male mojosari ducks and 12 female mojosari ducks. The results showed that the treatment of dietary protein level in feed formulation that the treatments had significantly different effect (P